Melodiz 0.2: jogo para auxílio no desenvolvimento da percepção musical com recursos de gamificação - Gama, Thiago Dias de Carvalho Quaresma (Universidade Federal Rural do Semi-Árido, 2019)
Music perception is considered an important skill for the development of other musical skills. In this sense, this work aims to improve and evaluate a mobile application to help the development of musical perception. However, to avoid rework, this work will start with the Melodiz 0.1 application. To achieve this goal, users will be offered exercises based on the identification of notes, intervals and musical instruments. To motivate users, gamification strategies will be adopted. Finally, its validation is presented, which was given through a questionnaire to assess the level of user satisfaction about the proposed application.
Keywords: Desenvolvimento para dispositivos móveis; Educação musical; Gamificação; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO